Violation of childrens' rights in the war in Croatia: a psychological perspective - Vizek Vidović, Vlasta; Kuterovac-Jagodić, Gordana (2000)
The aim of the paper is to inform about the results of the longitudinal study of the war consequences on psychological well-being of children in Croatia. In the first part of the paper the legal framework is described that should ensure the protection of children in armed conflicts. In the scond part the main findings of the empirical study are presented. Also some guidelines for psychological interventions at the different institutional levels are described.
Projekt MZOS
ENG